2010
DOI: 10.1007/s11661-010-0185-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Galvanizing Heat Treatments on the Microstructure and Mechanical Properties of High Al-Low Si Transformation Induced Plasticity Steels

Abstract: Heat treatments were performed using an isothermal bainitic transformation (IBT) temperature compatible with continuous hot-dip galvanizing on two high Al-low Si transformation induced plasticity (TRIP)-assisted steels. Both steels had 0.2 wt pct C and 1.5 wt pct Mn; one had 1.5 wt pct Al and the other had 1 wt pct Al and 0.5 wt pct Si. Two different intercritical annealing (IA) temperatures were used, resulting in intercritical microstructures of 50 pct ferrite (a)-50 pct austenite (c) and 65 pct a-35 pct c. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 35 publications
3
36
0
Order By: Relevance
“…[16] However, it has been shown that the required microstructures and mechanical properties can be obtained when using IBT temperatures compatible with continuous galvanizing thermal cycles. [17][18][19] The selective oxidation of the alloying elements, Mn, Si, and Al, at the steel surface can result in poor reactive wetting during galvanizing. [20][21][22][23][24] These oxides can prevent Al in the Zn bath from reacting with metallic Fe on the steel substrate to form the Fe 2 Al 5 Zn x interfacial layer, resulting in bare spot defects in the Zn coating and overall poor coating quality.…”
Section: Introductionmentioning
confidence: 99%
“…[16] However, it has been shown that the required microstructures and mechanical properties can be obtained when using IBT temperatures compatible with continuous galvanizing thermal cycles. [17][18][19] The selective oxidation of the alloying elements, Mn, Si, and Al, at the steel surface can result in poor reactive wetting during galvanizing. [20][21][22][23][24] These oxides can prevent Al in the Zn bath from reacting with metallic Fe on the steel substrate to form the Fe 2 Al 5 Zn x interfacial layer, resulting in bare spot defects in the Zn coating and overall poor coating quality.…”
Section: Introductionmentioning
confidence: 99%
“…The integrated intensities of (200) ferrite peak and (111), (002) and (022) austenite peaks were used for evaluation. Carbon content in retained austenite was calculated when considering the effect of alloying elements, according to [1,27]: a = 3.572 + 0.0012 Mn − 0.00157 Si + 0.0056 Al + 0.033 C…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…In particular, it was determined that an IA microstructure of 50 pct c combined with a 120 second IBT produced optimal mechanical properties for the 1.0Al-0.5Si steel and a 50 pct c IA microstructure combined with either a 90 or 120 second IBT time produced optimal properties for the 1.5Al steel. [17] However, Bellhouse and McDermid [17] did not investigate the effect of heat treatment parameters for the preceding alloys on the RA to martensite transformation kinetics during deformation and this is the focus of the present research. In this case, the term ''kinetics'' is used to describe the transformation of RA to martensite as a function of the applied deformation.…”
Section: Jr Mcdermid Hs Zurob and Y Bianmentioning
confidence: 96%
“…[5][6][7][8][9][10][11][12][13][14][15][16] In particular, the present authors have successfully coated two high Al, low Si (0.20C-1.5Mn-1.0Al-0.5Si and 0.20C-1.5Mn-1.5Al (wt pct)) steels [14][15][16] for which very good mechanical properties were also obtained. [17] A further challenge of processing TRIP-assisted steels within the CGL concerns the thermal cycles commonly used. For example, the IBT for TRIP-assisted steels is commonly carried out at temperatures between 643 K and 703 K (370°C to 430°C), [6] which is incompatible with the temperature of the molten zinc bath, which is typically 733 K (460°C).…”
Section: Jr Mcdermid Hs Zurob and Y Bianmentioning
confidence: 99%
See 1 more Smart Citation